New insights into the diversity and distribution of Leptanillinae (Formicidae) within China - Hamer, Matthew T.; Weemaels, André Ibáñez; Fu, Yifan; Xuan, Liu; Tse, Cheung Yau Leo; Tang, Kit Lam; Guénard, Benoit (Zootaxa, 2024)
Leptanillinae is an ant subfamily of low taxonomic diversity and limited distribution within the Old World. Species within this subfamily are hypogaeic and are notoriously difficult to find and collect. As a result of their rarity, comparatively little is known about their natural history and distributions. Based upon new sampling efforts, we present significant new records of Leptanillinae from Mainland China, and Hong Kong SAR. Opamyrma hungvuong Yamane et al., 2008 is newly recorded from Sichuan Province, alongside a potential easterly record from Zhejiang Province, greatly extending its northern and eastern range distribution. Further, Protanilla lini Terayama, 2009 is recorded from Mainland China for the first time from Fujian Province and Hong Kong. We provide detailed collecting accounts for all newly recorded species, including associated habitat, nesting locality, colony composition, and for P. lini dietary information. All new localities for both species significantly extend their previously assumed distributions. Additional records of Leptanilla bethyloides Griebenow, 2024, and a note on L. japonica Baroni Urbani, 1977 from Hong Kong are provided. An updated distribution checklist of Leptanillinae from Mainland China and Taiwan is also provided. Our new records point towards an under sampled ant fauna of Mainland China underlying the need for new sampling approaches within the region.